2008
DOI: 10.1007/s11695-008-9568-x
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and Obestatin Levels in Severely Obese Women Before and After Weight Loss After Roux-en-Y Gastric Bypass Surgery

Abstract: In contrast to previous weight loss studies involving gastric banding, ghrelin levels decreased and obestatin levels remained stable after massive weight loss in long-term follow-up. The favorable gastrointestinal hormone profiles observed are likely to contribute to the long-term weight loss success rate attributed to RYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 40 publications
2
34
1
5
Order By: Relevance
“…Many studies have shown gastric bypass operations to be associated with significant reduction of ghrelin levels (Cummings et al, 2002a;Geloneze et al, 2003;Lin et al, 2004;Roth et al, 2009;Stylopoulos et al, 2005;Suzuki et al, 2005). In addition, the normal, meal-related fluctuation and the diurnal rhythm of ghrelin level was found to be absent after gastric bypass surgery (Cummings et al, 2002a).…”
Section: Ghrelin and Bariatric Surgerymentioning
confidence: 99%
“…Many studies have shown gastric bypass operations to be associated with significant reduction of ghrelin levels (Cummings et al, 2002a;Geloneze et al, 2003;Lin et al, 2004;Roth et al, 2009;Stylopoulos et al, 2005;Suzuki et al, 2005). In addition, the normal, meal-related fluctuation and the diurnal rhythm of ghrelin level was found to be absent after gastric bypass surgery (Cummings et al, 2002a).…”
Section: Ghrelin and Bariatric Surgerymentioning
confidence: 99%
“…Haider and colleagues 149 showed that obestatin is lower in obese patients compared with lean controls and is increased 6 months after AGB. In contrast, Roth and associates 126 found that obestatin levels did not change 2 years after RYGB in spite of the massive weight loss of 62.5% EWL.…”
Section: Other Hormonesmentioning
confidence: 86%
“…In this situation, postsurgical weight loss caused different fluctuations in ghrelin levels: either an increase 65,66 or a decrease in plasma ghrelin 67,68 or, in some cases, no changes. 69 This variability in circulating ghrelin levels after metabolic surgery attracted the interest of numerous research teams in attempting to elucidate the mechanisms of postoperative weight loss.…”
Section: Ghrelin and Weight Statusmentioning
confidence: 99%